Changes in mental and sexual health among MSM using HIV pre-exposure prophylaxis during the SARS-CoV-2 pandemic: longitudinal analysis of the SwissPrEPared cohort study (Swiss Medical Weekly, 2022)
BACKGROUND: Changes in mental and sexual health among men having sex with men (MSM) due to the SARS-CoV-2 pandemic remain unclear.METHODS: Design: Longitudinal analysis of an ongoing, multicentre, pre-exposure prophylaxis (PrEP) cohort (NCT03893188) in Switzerland. Participants: HIV-negative MSM aged ≥18 who completed at least one questionnaire before and one after the start of the SARS-CoV-2 pandemic. Outcomes: Primary: mental health, defined as anxiety and depression scores assessed by the Patient Health Questionnaire-4. Secondary: sexual behaviour, well-being, PrEP use and disruption of care. Outcomes were assessed over seven periods corresponding to different SARS-CoV-2 prevention measures in Switzerland. We performed pairwise comparisons between periods (Wilcoxon signed rank test).RESULTS: Data from 1,043 participants were included. Whilst anxiety scores remained stable over time, depression scores worsened in the second wave and the second lockdown period compared to pre-pandemic scores. This was confirmed by pairwise comparisons (pre-SARS-CoV-2/second wave and pre-SARS-CoV-2/second lockdown: p